Real-world study of PD-1/L1 immune checkpoint inhibitors for advanced non-small cell lung cancer after resistance to EGFR-TKIs - Wei, Kunchen; Zhou, Chao; Chen, Yang; Feng, Xiao; Tang, Hao (Frontiers in Oncology, 2023)
Background Programmed cell death-1 (PD-1) and its ligand 1 (PD-L1) inhibitors have achieved good efficacy and safety in patients with advanced EGFR mutation-negative non-small cell lung cancer (NSCLC), but their efficacy in patients with previous EGFR mutations is limited. The aim of the present study was to explore the efficacy of PD-1/L1 immune checkpoint inhibitors for the treatment of patients with advanced NSCLC who are resistant to EGFR-TKIs Methods This retrospective study included 123 patients with stage IV NSCLC who received treatment in Shanghai Changzheng Hospital between January 2019 and January 2022 after failure of first-line EGFR-TKIs. Of them, 39 received ICIs + chemotherapy and anti-angiogenic drugs (ICIs+BCP group), 51 received ICIs monotherapy (ICIs group), and 33 received chemotherapy and anti-angiogenic drugs (BCP group). The gender, age, smoking history, ECOG score, EGFR mutation type, PD-L1 TPS expression, and the first routine blood index before second-line treatment of all enrolled patients were recorded, and their clinical outcomes and prognosis factors were analyzed. Results There was no significant difference in the objective response rate (ORR) and disease control rate (DCR) between the three groups. Patients in ICIs+BCP group had better prognosis than those in ICIs monotherapy group (PFS:9.5 vs. 4.64 months, p<0.001; OS: 16.97 vs. 7.9 months p<0.001) or BCP group (9.5 vs. 6.48 months, p<0.005; OS: 16.97 vs. 11.39 months p<0.005). Conclusion Our findings suggest that in the real-world practice in China, PD-1/L1 immune checkpoint inhibitors combined with chemotherapy and anti-angiogenic drugs are effective for the treatment of patients with advanced NSCLC who are resistant to EGFR-TKIs.